2018
DOI: 10.1515/kbo-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Terrorism Motivation Determinants

Abstract: In its essence, terrorism is a human destructive activity and as such it is characterized by certain motives, needs, etc. It is important for the researchers to analyze in detail the needs that underlie normal human functioning and those that determine terrorism and integration into a terrorist organization. It is quite possible that such a research approach leads to the conclusion that they are not principally, qualitatively different, rather the needs of the terrorist are hypertrophied basic human needs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…According to the Dutch intelligence and security service, some returnees were disappointed with what they experienced in Syria (AIVD, 2014). Disillusionment with violence and a desire for a normal life can prevent individuals from displaying violent extremist behavior (Krastev, 2018; Lösel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the Dutch intelligence and security service, some returnees were disappointed with what they experienced in Syria (AIVD, 2014). Disillusionment with violence and a desire for a normal life can prevent individuals from displaying violent extremist behavior (Krastev, 2018; Lösel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that violent extremists comprise a heterogeneous group that cannot be characterized by a typical profile of a terrorist offender (Bakker, 2006; Van Leyenhorst & Andreas, 2017; Vidino & Hughes, 2015). Terrorist acts are mainly ordinary crimes that are referred to as terrorism because of the motivation of the perpetrator (Krastev, 2018). To understand the diversity in violent extremists, it is essential to first explore the motivations that may underlie violent extremism and radicalization (Subramanyam, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations